Efeitos da dieta à base de okara sobre o intestino e o gasto energético de ratos submetidos à restrição proteica na vida intrauterina e lactação e recuperados após o desmame - Lima, Faena Moura de (2013)
In previous work we demonstrated by biochemical and hormonal parameters that the okara as protein source possesses efficiency of nutritional recovery similar to diet based on casein, however, treatment with diet okara, independent of nutritional status, reduced food intake and the final body weight in addition to changing the volume and fecal consistence. Thus, in order to elucidate whether the lower final body weight could be justified only by the reduction of food intake and to verify the intestinal effects of the consumption of okara, we evaluated factors associated with energy expenditure and the intestine in this animal model. Only male rats from mothers that were fed either 17% or 6% protein during pregnancy and lactation were maintained on a 17% casein (CC and LC), 17% okara (CO and LO) or 6% casein (LL) diet after weaning until adult age. The nutritional recovery, independent of protein source, reduced the levels of triiodothyronine (T3), however increased the levels of thyroid stimulating hormone (TSH), decreased hyperphagia and increased weight observed in animals under protein restriction. Rats fed with okara based diet exhibited reduced the total food intake, smaller weight gain and also the cecum presented low values of pH compared to animals fed with casein. These animals showed higher lipids intake, the mRNA expression of PGC1α and UCP1 in interscapular brown adipose tissue, the adaptive thermogenesis and the ex vivo lipolysis rate stimulated on epididymal adipose tissue. In conclusion, we have demonstrated that the subproduct okara is efficient on weight control and reduction of fat deposits on animals recovered from malnutrition, even without increasing the energy expenditure, besides promoting beneficial intestinal effects despite the nutritional status.